Abstraction & Economy myths of growth - Stadler, Eva Maria 1964-; Tischer, Jenni 1979- (De Gruyter, 2024)
Opposing a regime of accumulation and abstraction This anthology explores the tension between abstraction and economics from the perspectives of art, art theory, art history, as well as law, sociology, philosophy, and economics. It poses questions about the current challenges of a global capitalist economy with claims to expansive growth in relation to aesthetics, technology, and democracy. The relationship between abstraction and economics is discussed in a series of theoretical and artistic contributions. The main focus is on the role of art in mediating between the concrete and the abstract, on formalist approaches to art theory, and on the social and economic cues that help us trace the aesthetic regime of capitalism. Ultimately, this book asks, "how can artistic-aesthetic practices counteract the regime of accumulation and abstraction?" The visual arts in a socioeconomic context Reflecting on the relationship between abstraction and economics from capitalist-critical, decolonial, ecological, and queer-feminist perspectives Contributions by Brenna Bhandar, Christina von Braun, Sabeth Buchmann, Denise Ferreira da Silva, Sven Lütticken, R. H. Quaytman, Marina Vishmidt, and others
Description based on online resource; title from PDF title page (publisher's Web site, viewed 02. Jun 2024)
Keywords: Bildende Kunst; Kapitalismus; Kunstgeschichte; Kunsttheorie; Recht; Soziologie; Ökonomie; ART / Criticism; Technologie; Wirtschaft; Abstraktion; Ästhetik; Demokratie; Kunst; Globalisierung; Ausstellungskatalog -- Universitätsgalerie der Angewandten im Heiligenkreuzerhof -- 12.03.2022-09.04.2022 -- Wien; Ausstellungskatalog -- 27.04.2024-01.09.2024 -- Lauffen, Bad Ischl; Konferenzschrift -- 2022 -- Wien